Perbandingan Performance Kriptografi RSA, RSA-CRT, Rabin dalam Proses Pengamanan Pesan Berbasis Teks - Manalu, Deby Cynthia Rohara; Mutiara Enjelina; Sipayung, Johannes Bastian Jasa (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2024)
Data security is a critical aspect in the digital era, especially in securing text-based messages. This research compares the performance of three asymmetric cryptography algorithms-RSA, RSA-CRT, and Rabin-in terms of the speed and efficiency of the encryption and decryption process. The RSA (Rivest-Shamir Adleman) algorithm, one of the most popular cryptographic methods, uses two different keys (public and private) to encrypt and decrypt data, but has a weakness in decryption time efficiency on large data. RSA-CRT, as a modification of RSA with the Chinese Remainder Theorem approach, speeds up the decryption process by dividing large operations into smaller ones. Rabin's algorithm, which is based on prime factorization, shows high time efficiency for both encryption and decryption processes, although it produces four possible plaintexts that require additional selection. All three algorithms were tested using text data with varying character sizes, ranging from 100 to 10,000 characters. The test results show that RSA has the fastest encryption time, RSA-CRT excels in decryption, and Rabin offers the best overall efficiency for securing text-based data. This research provides algorithm recommendations according to system needs, taking into account the balance between efficiency and security.